Comparing clinical, laboratory, and epidemiological features of COVID-19 variants during different pandemic waves among children in Ukraine - Harashchenko, Tetiana; Umanets, Tetiana; Livshits, Ludmila; Volodymyr, Lapshyn; Antypkin, Yurii (Paediatrica Indonesiana, 2024)
Background The SARS-CoV-2 virus, the causative agent of the coronavirus disease (COVID-19), mutated during its replica-tion and spread among the population. These mutations led to new viral variants, which differed in their characteristics and manifestations, contributing to the wave-like progression of the COVID-19. The Centers for Disease Control and Prevention classified variants based on the public health risk include variants of interest such as λ and μ, variants of concern including α, β, γ, δ, ο, variants of high consequence, and variants being monitored. Objective To conduct a comparative analysis of the demographic, clinical, epidemiological, radiological, and laboratory character-istics of hospitalized children with COVID-19 during different waves of the disease. Methods A cohort study was conducted involved 337 children aged one month to 18 years who were hospitalized with laboratory-confirmed COVID-19 between 2020 and 2023 in Ukraine. Results During wave 3 (W3), wave 5 (W5) and wave 6 (W6), children under 3 years of age were hospitalized more frequently. The severe course of disease predominantly occurred during W3 period, with 47.3% cases demonstrating severe symptoms such as respiratory failure, bilateral pneumonia, and significant changes in laboratory parameters, including white blood cell count, eryth-rocyte sedimentation rate, D-dimer, and procalcitonin. One fatal case was reported during W3. The duration of hospitalization was longest for children in the W3 group. A moderate course of the disease was significantly more prevalent among hospitalized children in the first wave (77.78%, P<0.05), characterized by interstitial changes in the lungs, elevated C-reactive protein, and platelet levels. Fever and intoxication syndrome were reported with similar frequency during all waves of COVID-19. Conclusion Our study demonstrates the dynamic changes in manifestations and the progression of the disease across different variants of concern of SARS-CoV-2. The most severe cases of COVID-19 was observed during the third wave which predominated by the δ (delta) strain.